Estimating Observer and Data Reputation in Mariner Volunteered Bathymetry - Calder, Brian R. (The International Hydrographic Review, 2021)
Volunteered Bathymetric Information (more commonly called Crowd-sourced Bathymetry, CSB) has the potential to assist authoritative charting but a lack of formal assessment methods has limited uptake of this idea. This paper proposes a reputation system for observers (and data) to estimate the observer’s ability to match authoritative depths; a time-sequence estimate of vertical bias is also computed. This reputation can form the basis for decisions on how many observations are required from a VBI source before charting actions could be considered. Using data from the IHO DCDB and NOAA surveys from the Puget Sound area (U.S. west coast), bias estimate and reputation assessment are demonstrated for archetypal observers.